PELATIHAN TAKSONOMI NUMERIK SEBAGAI STRATEGI UNTUK MENINGKATKAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE GURU BIOLOGI - Amalianneisha Rafadewi Andhanatami Putri; Topik Hidayat; Widi Purwianingsih (Jurnal Pendidikan Sains Indonesia, 2019)
TPACK is the ability to integrate knowledges of content, pedagogical, and technology that must be possessed by teachers in facing the era of education in the 21st century. To improve TPACK can be done with training strategies, in this study numerical taxonomy training is a training program for biology teachers about TPACK and CoRes, and content which is related to concepts, technology, and learning strategies for classification of living things that discuss about numerical taxonomy, as a strategy to improve TPACK biology teachers in classifying living things learning. The method used was pre-experimental one group pre-post test design. The data about teachers’ TPACK was gained from CoReS and lesson plans prepared by teachers, and teachers’ prespective on TPACK was gained from responses toward questionnaires. The result showed after training,  analysis of CoRes reveals that 80% of Biology teachers’ is on the Growing TPACK, and 20% is on the Pre TPACK category. The average percentage of N-gain TPACK ability of teachers is 60% in the medium category, the result of significant test (t test) indicates t score t table (16.88 2.13), it showed a significant difference in the TPACK ability of biology teachers before and after numerical taxonomy training. Teachers’ prespective on TPACK in classification of living things learning have a positive changes, teachers starts to be able to determine the technology, strategy, and understanding the content of living things learning especially the numerical taxonomy. It can be concluded that numerical taxonomy training can improve TPACK’s ability.